2022
DOI: 10.1007/s42978-022-00178-w
|View full text |Cite
|
Sign up to set email alerts
|

Physical Characteristics Explain Ball-Carrying Capability in Sub-Elite Rugby Union Players

Abstract: Purpose The aims of the present study were two-fold: (i) to investigate the relationship between physical characteristics and the game statistics associated with ball-carrying capability amongst sub-elite rugby union players, and (ii) to predict the level of change in these physical characteristics required to improve the associated game statistic via regression analysis. Methods Thirty-eight senior professional players (forwards, n = 22; backs, n = 16) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Despite this, Cunningham et al (14) identified no relationship between 10-m sprint momentum and ball-carrying capability among international rugby union forwards. However, 10-m sprint momentum may not be an applicable measure for the forward positions (27) because time-motion analysis has demonstrated that forwards typically perform a greater number of shorter distance sprints during a match in comparison to backs (3), with an average distance per sprint of <10 m (20). Therefore, 5-m sprint momentum may possess greater associations with ball-carrying capability among the forwards, a hypothesis that future research should investigate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this, Cunningham et al (14) identified no relationship between 10-m sprint momentum and ball-carrying capability among international rugby union forwards. However, 10-m sprint momentum may not be an applicable measure for the forward positions (27) because time-motion analysis has demonstrated that forwards typically perform a greater number of shorter distance sprints during a match in comparison to backs (3), with an average distance per sprint of <10 m (20). Therefore, 5-m sprint momentum may possess greater associations with ball-carrying capability among the forwards, a hypothesis that future research should investigate.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, sprint times over 5-40 m have presented weak-to-strong correlations with the number of tries scored, line breaks, tackle breaks, defenders beaten, and meters advanced per carry among international rugby union (14,54) and rugby sevens players (49). In addition, Hart et al (27) concluded that improvements in lower-body relative strength, acceleration performance, and position-specific alterations in body mass are required to maximize the ballcarrying capability of subelite ruby union players because of the large associations observed between these physical measures and game statistics. These studies can provide objective data to inform the development of specific physical characteristics with the fundamental aim of optimizing the transfer of these physical qualities to on-field ball-carrying performance.…”
Section: Introductionmentioning
confidence: 99%